Theologians as Cultural Brokers: Transatlantic Translation of Ideas during the Emergence of Liberation Theology - Schnoor, Antje (Religions, 2021)
The paper sheds light on the transatlantic theological discourse during the emergence of liberation theology. It conceptualizes this discourse as a transatlantic communication process reframing it as a transfer and translation of ideas and concepts. Starting from this perspective, I prove the assumption that the transatlantic theological discourse reflected a Latin American claim to academic equity and I show that European reactions to liberation theology implied answers to that claim. As the focus is on the relationship between Latin America and Europe, the article illustrates the significant role of relationships marked by different forms of dependency (economic, political, intellectual) in the development of liberation theology. Furthermore, the paper argues that for a deeper understanding, it is misleading to speak about Latin American theologians on the one hand and European theologians on the other hand, as if it was about clear-cut groups with homogenous motivations, positions, and goals. On the contrary, there were advocates and opponents of liberation theology on both sides of the Atlantic who moreover formed transatlantic alliances. The paper calls those theologians cultural brokers, since they communicated and mediated across the Atlantic.